English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Hi I'm reading my textbook on first order diff equation and i cant see to get the algebra from this part.

y'/x^2 - 2y/x^3 = ....

d/dx [y/x^2] = ...

How does that work out? Can someone explain.

2007-02-20 16:46:16 · 1 answers · asked by eeeek 1 in Science & Mathematics Mathematics

1 answers

Reverse the equations and you have differentiation by chain rule:
d/dx [y/x^2] =
d/dx[yx^-2] =
-2yx^-3 + y'x^-2 =
y'/x^2 - 2y/x^3

2007-02-20 17:03:24 · answer #1 · answered by Helmut 7 · 0 0

fedest.com, questions and answers